Anathan-Jacobs Grand Trunk Pacific Railway Collection - Jacobs, Norman Leonard, 1885- (1905)
Norman Leonard Jacobs was an engineer and surveyor with the Grand Trunk Pacific Railway in Canada. The collection consists of his correspondence with Bessie Frank (later Anathan), an acquaintance from Pittsburgh. Jacobs wrote of daily life in Canadian cities like Winnipeg and Edmonton, interactions with First Nations, and daily hardships encountered in the field (extreme cold, snowblindness, and lack of food), but also spoke of his work with pride and enthusiasm. In addition to the letters, Jacobs wrote twenty-eight pages of a "Diary of a Tenderfoot." Also included in the collection are two photobooks and various loose photographs, which display various aspects of camp life, details of work sites and the Canadian landscape, and First Nations peoples. Some of the photographs are extremely faded. Native peoples mentioned include Ojibwe, Blackfoot, Cree, "Surteau" (like Saulteaux),"Bloods" (Kainai), and "Stonies" (Nakoda, or "Stoney"). The images include family groups; men, women, and children fishing; men (some apparently hired by Jacobs or his company to act as guides and carriers in the field) working with an infant in a cradleboard; Ojibwe graves; tepees [tipis]; "Sioux" warriors; a sweat bath; horse races; individuals like Joe KaeKwitch, Chief Handorgan, Chief Wingard, etc. Most of these materials have been digitized and are available through the APS's Digital Library. Also see the finding aid for more background information on Jacobs and detailed itemized lists for both Series I. Correspondence and Series II. Graphic Materials.